Labelling Antibodi Anti-TPO Menggunakan Alkaline Phosphatase (AP) Untuk Deteksi Autoantibodi TPO Pada Serum Pasien Autoimmune Thyroiditis Disease (AITD) Menggunakan Dot-Blot - Nurmahdi, Hilman; Aulanni'am, Aulanni'am; Mahdi, Chanif (Jurnal Ilmu Kimia Universitas Brawijaya, 2013)
Autoimmune thyroiditis disease (AITD) is an organ specific autoimmune disorder which commonly found in the world. Presence of Thyroid Peroxidase (TPO) enzyme in AITD patient is often used as biomarker in AITD diseases. The aims of this research is done by labelling a polyclonal antibody against autoantibody TPO using Alkaline Phosphatase that used to detect autoantibody TPO in AITD patient using direct Dot Blot method. The protein of Autoantibody TPO is isolated from human AITD sera and has molecular weight of 51.1 kDa. This has been confirmed by western blot using monoclonal antibody standard for TPO. Autoantibody TPO is used as an antigen to produce polyclonal antibody against autoantibody TPO in rabbbit (Oryctolagus cuniculus).  The result of this research shown that autoantibody TPO is immunogenic that could stimulate immune system to produce polyclonal antibody against autoantibody TPO. The highest titer of polyclonal antibody against autoantibody TPO from rabbit sera has optical density of 1,75 using ELISA method. The result of Dot Blot showed that polyclonal antibody which labelled with Alkaline Phosphatase, is able to recognize autoantibody TPO  in patient sera and have the highest colour intensity on the third bleeding.Key words : AITD, Alkaline Phospahatase, autoantibody TPO, Dot Blot, ELISA